Case report: Primary alveolar soft-part sarcoma of the lung in a child - Xu, Zhufei; Wang, Jinhu; Mao, Junqing; Xu, Dan; Wu, Lei; Zhou, Yunlian; Li, Xuejing; Chen, Zhimin; Wang, Yingshuo (Frontiers in Surgery, 2023)
The alveolar soft-part sarcoma involving the lung is mostly metastatic, while the primary alveolar soft-part sarcoma involving the lung occurs more rarely. Herein, we reported on a rare case of primary alveolar soft-part sarcoma of the lung, which might be with the earliest onset reported thus far. In this report, surgery was used to excise the lesion as much as possible, and its combination with chemoradiotherapy and anti-angiogenic agent may provide an important reference for the development of standard treatment or first-line treatment for these children patients.